ANALISA SISTEM PEMELIHARAAN ALAT TENSIMETER - Sri Ayu Tugi Astuti; Hotromasari Dabukke (Prodi Teknik Elektromedik Universitas Sari Mutiara Indonesia, 2020)
The purpose of this study was to determine how the implementation of the tensimeter maintenance system at the Simpang Dolok Health Center Laboratory. This research is a qualitative descriptive study. The data was collected through tensimeter maintenance techniques. So that the Simpang Dolok Community Health Center performs routine cleaning and maintenance of the tensimeter in order to make the tensimeter last longer during its serviceable period. It is recommended that the head of the Simpang Dolok Health Center Laboratory room pay attention to the equipment maintenance system.